2017
DOI: 10.1080/23322039.2017.1317117
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, research and development volatility and firm performance - Evidence from Spain and Ireland

Abstract: The present study sheds light on the comparative experiences of the two countries originating from differing legal systems and describes how their codes and practices affect the publicly listed firms’ performance. It investigates the linkages between Research and Development (R&D) expenditures, Board characteristics and firm performance using a sample of Irish and Spanish firms for the period 2005–2014. To do this, the study uses ROA and Tobin’s Q as proxies for financial performance; and board size, non-execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…There are many studies to support the theoretical arguments, e.g. Pham (2016) and Duppati et al (2017) demonstrate the positive effect of smaller boards on shareholder value as measured by ROA, ROE, and Tq.…”
Section: Board Size and Shareholder Valuementioning
confidence: 94%
See 1 more Smart Citation
“…There are many studies to support the theoretical arguments, e.g. Pham (2016) and Duppati et al (2017) demonstrate the positive effect of smaller boards on shareholder value as measured by ROA, ROE, and Tq.…”
Section: Board Size and Shareholder Valuementioning
confidence: 94%
“…Over the decades, extensive research has been undertaken in developed markets (e.g. Bansal & Sharma, 2016;Pham, 2016;Duppati et al, 2017;Yasser et al, 2017;Gafoor et al, 2018;Kabir et al, 2019;Almoneef & Samontaray, 2019;Majeed et al, 2020) and emerging market economies, like Bangladesh (e.g. Al Farooque et al, 2007;Ahmed, 2010;Muttakin & Ullah, 2012;Hossain, 2020), attempting to prove the efficacy of country-level corporate governance structures in enhancing firm performance or creating value for shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…A significant stream of research discusses the tendency of managers to resort to deceitful practices, adjusting or reducing R&D expenditure to smooth earnings, when they anticipate that the expected financial results will not meet analysts' forecasts, the company faces financial constraints or for other personal reasons (Tong & Zhang, 2014;Xiang et al, 2020). Duppati et al (2017) talk about the myopic behaviour of managers, with reference to their decision to frequently reduce the level of R&D expenditure in favour of short-term results, sacrificing the long-term value of companies. Tong and Zhang (2014) infer that the capital market penalises managerial myopia, especially in companies with complex R&D investments.…”
Section: Literature Review and Hypotheses Development 1volatility Of ...mentioning
confidence: 99%
“…The magnitude and impact of the R&D volatility on the market value of companies have been highly explored by researchers over the last two decades (Duppati et al, 2017;Lakhal & Dedaj, 2020;Patel et al, 2018;Xiang et al, 2020). The difficulty in demonstrating the link between the volatility of R&D expenditure and the value of the company means that this topic continues to be of interest in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The UK CG Code 2014 encouraged females to participate on boards to increase effectual functioning and maintain good relationships with stakeholders (Jizi, 2017). Duppati et al (2017) reported that Spain implemented a law on gender equality on boards especially for larger companies with an excess of 250 employees which are listed on IBEX 35. This law emphasises that women should be appointed on company boards until an even number of both genders has been achieved.…”
Section: Women On Board and Sdmentioning
confidence: 99%